Enhancing Public Service Quality in Makassar City: Examining from Population and Civil Registration Office - Rifai Rifai; Taufik Irfadat (FISIP Universitas Islam Negeri Raden Fatah Palembang, 2023)
Public services are an important part that needs to be considered in the development of autonomy because in addition to being in accordance with the basis of reform in the field of government, it is also directly related to the welfare of the community, services to the community have become the main thing. Objective in organizing public administration. The purpose is to find out the optimization of public services, at the population and civil registration office of the city of Makassar, as for the results of the research, namely by presenting a bus car as a Mobile Population and Civil Registration unit can reach people who are constrained by distance, and travel costs, as a concrete configuration of services provided by public service providers to accelerate services without having to go to the relevant offices. to make submissions. To make a submission. Application for issuance of population and civil registration documents. There is an attitude statement given by the Makassar City Population and Civil Registration Office in the form of a statement that reads